Business Strategy, ISO 31000 and Bankruptcy Risk - Lu'lu'ul Jannah; Ridho Muhammad Purnomosidi (Inovbiz: Jurnal Inovasi Bisnis, 2021)
The purpose of this study is to examine the effect of business strategy to bankruptcy risk and the effect moderate of ISO 31000 to business strategy and bankruptcy. The sample of this study is 50 firms listed on the Indonesia Stock Exchange (IDX).  the results support that business strategy has a significant effect on bankruptcy risk. Firms which implement either one of two generic business strategies of cost leadership or differentiation, sig-nificantly effect to the risk of bankruptcy. the second result is ISO 31000 has not effect moderated to business strategy and bankruptcy risk